Dakwah Majelis Ulama Indonesia dan Perubahan Iklim - Abdurrahman Hilabi (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2020)
Climate change is due to global warming, global warming is an increase in the average temperature of the atmosphere, sea and land. Global warming is caused by the greenhouse effect. The greenhouse effect itself is caused by an increase in the concentration of carbon dioxide (CO2) and other gases in the atmosphere. If every Muslim has awareness of his obligations as khalifatullah fil Ard, then it is not a difficult matter for Muslims to initiate and preach the importance of maintaining environmental balance to all corners of the world, including industrial-capitalist countries that contribute a lot of carbon dioxide gas emissions that trigger global warming - jointly committed to maintaining environmental balance. Thus, global warming on earth can be stopped.